Tracing the Past, Shaping the Future: Latin American Constitutionalism and Its Discontents - Interview With Professor César Landa (Alternautas, 2025)
Professor César Landa, a renowned constitutional law scholar and distinguished public servant in Peru, is one of the unique figures who successfully bridges the worlds of academia and political practice. In addition to his academic position as a professor of constitutional law, he has held several key state offices, including President of the Peruvian Constitutional Court, ad hoc judge of the Inter-American Court of Human Rights, Deputy Minister of Justice, and Minister of Foreign Affairs. Drawing on this unique combination of experience, Professor Landa offers a rich and informed perspective on the democratic challenges facing Peru and Latin America more broadly. At a time when democratic erosion and the crisis of representative institutions have become global phenomena, his reflections on institutional fragility, constitutional resilience, and the potential for democratic renewal have both scholarly and practical significance. This interview aims to contribute to the broader conversation on constitutionalism in the region and to bring Professor Landa’s deep insights into the academic literature.